ChemInform Abstract: Scope of the Palladium‐Catalyzed Aryl Borylation Utilizing Bis‐Boronic Acid. Issue 2 (9th January 2013) - Molander, Gary A.; Trice, Sarah L. J.; Kennedy, Steven M.; Dreher, Spencer D.; Tudge, Matthew T.
Abstract A greener and more economical method compatible with a wide range of substrates is presented for the title reaction by using bench stable and commercially available reagents.